Aeroplane design study STOL airliner (A71). Part 1- configuration description and data - Howe, D.; Ward, R. E. (Cranfield Institute of Technology; College of Aeronautics, 1972)
The interest in STOL airliners was reflected in the choice of a 100-118 passenger short range aircraft of this type as the 1971 design project. In addition to the use of the study for detailed investigation by the students of Aircraft Design it also served as the basis for an investigation of the low speed lift and control problems of STOL aircraft. This report is concerned with a description of the configuration adopted and specification of geometric and aerodynamic data. As such it is the first part of the complete reporting of the investigation, subsequent parts being concerned with the more detailed work. The aircraft was designed to operate from 2000 ft long single runways and have a cruising speed of up to 11 - 0.83 at 30,000 ft altitude. The estimated gross weight is 115,000 lb and when landing at 100,000 lb weight the approach speed is 79 knots. The high lift coefficients necessitated by this are obtained either by externally blown jet flaps or an augmenter wing arrangement.